Health sciences seeking behavior of Filipinos with diabetes - De Leon, Jude Miguel H. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Type 2 diabetes is one of the leading chronic diseases in the Philippines, with millions of Filipinos diagnosed thus far. Understanding that health information-seeking behavior of Filipinos with diabetes, a relatively unexplored topic, is crucial in effectively educating diabetes patients and preparing them in maintaining their health and condition. Using snowball sampling, 29 respondents were contacted and surveyed about their age, sex, education income, religion, address, as well as their preferred and most frequently actively accessed or passively received health information sources. The results were tallied and ranked according to their most preferred sources. Fisher's Exact test of independence was used to determine if there was any relationship between contextual factors, namely demographics and location, and the frequency of which the respondents actively accessed or passively encountered health information from the sources. Doctors, family members, other person with diabetes, and friends, or neighbors ranked overall highest as the preferred sources, but few relationships were found between contextual factors and health information access frequency, whether passive or active. In spite of preconceived notions, only two respondents expressed confidence in albularyos and hilot. Respondents were generally untrusting of health information sources outside of their doctors and immediate social circle. T.V. and radio programs were the second most frequency cited passive source, but trust and use of information from it are middling. The study concludes that since the trust and confidence of respondents. Mostly resides within the diabetic community, whether it includes family members or otherwise, and doctors, better counseling and thorough discussion from doctors and professionals about diabetes is recommended. Local communities are also encouraged to bolster barangay health services and its presence to increase confidence in them, as well as take a proactive approach to community awareness.